2017
DOI: 10.1111/mec.14357
|View full text |Cite
|
Sign up to set email alerts
|

Adult plasticity in African cichlids: Rapid changes in opsin expression in response to environmental light differences

Abstract: Phenotypic plasticity allows organisms to adapt quickly to local environmental conditions and could facilitate adaptive radiations. Cichlids have recently undergone an adaptive radiation in Lake Malawi where they inhabit diverse light environments and tune their visual sensitivity through differences in cone opsin expression. While cichlid opsin expression is known to be plastic over development, whether adults remain plastic is unknown. Adult plasticity in visual tuning could play a role in cichlid radiations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 108 publications
5
62
0
Order By: Relevance
“…In particular, it is the opsins at either end of the light spectrum that are affected: deep‐reared fish expressed more LWS, and shallow‐reared fish expressed more SWS2a. This follows previous work showing plasticity in cichlid visual development (Hofmann et al, ; Nandamuri et al, ; Smith et al, ; Van der Meer, ). In contrast with prior studies, however, our light manipulations were relatively subtle, mimicking the natural spectral (and partly intensity) differences in Lake Victoria.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, it is the opsins at either end of the light spectrum that are affected: deep‐reared fish expressed more LWS, and shallow‐reared fish expressed more SWS2a. This follows previous work showing plasticity in cichlid visual development (Hofmann et al, ; Nandamuri et al, ; Smith et al, ; Van der Meer, ). In contrast with prior studies, however, our light manipulations were relatively subtle, mimicking the natural spectral (and partly intensity) differences in Lake Victoria.…”
Section: Discussionsupporting
confidence: 90%
“…A2‐based chromophores and the expression levels of the opsin genes (Carleton, ). Light‐induced changes in opsin expression have been observed in several fish species, including cichlids (Dalton, Lu, Leips, Cronin, & Carleton, ; Fuller & Claricoates, ; Fuller, Noa, & Strellner, ; Hofmann, O'Quin, Smith, & Carleton, ; Nandamuri, Yourick, & Carleton, ; Shand et al, ; Smith, Ma, Soares, & Carleton, ; Stieb, Carleton, Cortesi, Marshall, & Salzburger, ; Van der Meer, ; Veen, Brock, Rennison, & Bolnick, ). This provides an experimental opportunity to manipulate visual system development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using L. goodei (Fuller & Claricoates, ) and cichlids (Nandamuri et al, ) that have indicated plasticity in opsin expression reported significant changes in opsin transcripts, measured by qPCR, within 3 days of exposure to new light regimes. Changes in LWS opsin transcript expression within cones has also been observed by in situ hybridization in cichlids after 6 months of light treatment (Dalton et al, ) and by immunolabelling of LWS opsin in M. atlantica after 4 months of treatment (Schweikert & Grace, ).…”
Section: Discussionmentioning
confidence: 71%
“…Besides genetically programmed opsin switches that occur during retinal development, studies on black bream Acanthopagrus butcheri (Munro 1949) (Shand et al, ), cichlids (Dalton et al, ; Härer et al, ; Nandamuri et al, ), bluefin killifish Lucania goodei Jordan 1880 (Fuller & Claricoates, ), guppies Poecilia reticulata Peters 1859 (Sakai et al, ) and Atlantic tarpon Megalops atlanticus Valenciennes 1847 (Schweikert & Grace, ) have shown plasticity in opsin gene expression in response to changes in the light environment. In guppies (Sakai et al, ) and the M. atlanticus (Schweikert & Grace, ), which seem to upregulate opsin gene products to match the dominant wavelengths of new spectral backgrounds, behavioural and electroretinogram observations suggest enhanced sensitivity to the prevalent spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we found that the LWS expression level was positively and negatively correlated with the male body redness across populations in Nomorhamphus ( Figure S4a) and in Oryzias ( Figure S4b), respectively. While opsin expression is known to be plastic in response to lighting environments (Nandamuri, Yourick, & Carleton, 2017), these findings indicate that the convergence of body colorations between F I G U R E 5 Correlation of (a) the population-mean male redness measured as the ratio of the red areas to the total body area and (b) the population-mean expression level of the LWS opsin genes (LWSa + b) between Nomorhamphus and Oryzias. While opsin expression is known to be plastic in response to lighting environments (Nandamuri, Yourick, & Carleton, 2017), these findings indicate that the convergence of body colorations between F I G U R E 5 Correlation of (a) the population-mean male redness measured as the ratio of the red areas to the total body area and (b) the population-mean expression level of the LWS opsin genes (LWSa + b) between Nomorhamphus and Oryzias.…”
Section: Discussionmentioning
confidence: 90%